Testicular oxidative stress in Sprague-Dawley rats treated with bitter melon (Momordica charantia): the effect of antioxidant supplementation - Yama, OE; Duru, FIO; Oremosu, AA; Noronha, CC (Bangladesh Journal of Medical Science, 2011)
Objective: An important mediator of testicular injury is oxidative stress; the implicating pathway has been pointed at a free radical mechanism by researchers. This article, investigates the effect of bitter melon (Momordica charantia) (MC) seed extract and antioxidant supplementation in the testes of Sprague-Dawley (S-D) rat. Methodology: Ninety male S-D rats, weighing between 110- 214 g, were assigned randomly into six main Groups A to F. Group A was administered 50 mg/100 g of MC extract orally, between 6 to 16 weeks. Group B were pre-treated with ascorbic acid (AA) 0.01mg/kg, three days/week, α-tocopherol (AT) 20 mg/kg, five days/week and both test solutions (TS) i.e. AA and AT; 0.01 and 20 mg/kg, three and five days/week for 8 weeks. This was followed by administration of the extract at dose and duration as in A. Group C received the extract for 8 weeks and afterwards post-treated for another 8 weeks with AA, AT and both TS (as above). Group D in addition to the extract administration were treated with AA, AT and both TS in dose and duration similar to B above. Group E had AA, AT and both TS alone for 8 weeks. Group F served as the control subjects. The animals testicular tissues were processed for malondialdehyde (MDA) and AA concentrations. Serum testosterone (TT) assay was done from left ventricular blood. Results: The extract administered for 6, 8 and 16 weeks produced significantly (p < 0.05) increased testicular MDA (1.74 ± 1.15, 1.84 ± 0.38 and 2.38 ± 0.40) compared to control (0.38 ± 0.02, 0.38 ± 0.03 and 0.35 ± 0.02) and decreased AA (0.01± 0.02, 0.01± 0.01 and 0.00± 0.01) compared to control (0.15 ± 0.02, 0.12 ± 0.02 and 0.13 ± 0.02). There was also an associated significant decrease (p < 0.05) in peripheral TT levels compared to control. The extract produced responses that showed no prophylactic rather modulatory effect with TS. Conclusion: These findings suggest that the extract resulted in changes in the testicular oxidative status. This may play a role in testicular dysfunction that may compromise fertility. Key words: Momordica charantia; malondialdehyde; ascorbic acid; testosterone. DOI: http://dx.doi.org/10.3329/bjms.v10i2.7805 Bangladesh Journal of Medical Science Vol.10 No.2 Apr’11 pp.104-111